Design of network architecture and method of bandwidth measure for IMS bearer network of State Grid - Zhenhua QU (Dianxin kexue)
The design of network architecture for IMS bearer network of State Grid was studied and analyzed,including the backbone of the network architecture and transition network architecture.And according to the network architecture,media flow and signaling flow,the IMS switching network on the data communication network backbone side,access side of the bandwidth requirements and measurement methods were put forward,which have a guiding significance for the construction of IMS bearer network of State Grid.